Implementasi Penyelenggaraan Pemanfaatan Ruang Pasca Omnibus Law Undang-Undang Cipta Kerja (UU Nomor 11 Tahun 2020 tentang Cipta Kerja dan Perubahannya Serta Turunannya) di Kabupaten Ogan Ilir - Puspasari, Rizka (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to describe and analyze the implementation of space utilization policies in Ogan Ilir Regency after the enactment of UUCK, as well as to describe and analyze obstacles in space utilization policies after UUCK. The research results show that the implementation of Edward III's policies consists of four dimensions, namely: communication, resources, disposition, and bureaucratic structure. The first dimension, communication, produces poor results because information about spatial planning changes has not been disseminated to the community in the form of socialization. The resources available to implement space utilization policies are insufficient. Several obstacles were found that hampered the implementation process, such as budget limitations, lack of qualified staff, and lack of community understanding due to lack of socialization and collaborative communication that was not effective enough.